THE IMPACT OF PROJECT-BASED LEARNING ON STUDENTS' SCIENTIFIC LITERACY AND AUTONOMY - Rediani, Ni Nyoman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Scientific literacy and autonomy are crucial for students to cope with 21st-century learning demands, where educators need to innovate the learning process. This serves as the rationale for analyzing the impact of Project-Based Learning (PjBL) on scientific literacy and autonomy among fourth-grade elementary school students. The research design employed a quasi-experimental design with a sample size of 58 participants. Data collection utilized both test and questionnaire methods. The test instrument consisted of 20 essay questions to assess scientific literacy, while the questionnaire comprised 30 statements to measure autonomy. Data analysis methods included quantitative descriptive analysis and inferential statistical analysis, employing MANOVA with a result of 0.00 < 0.05. Based on the analysis, Project-Based Learning (PjBL) significantly influences both scientific literacy and autonomy of the students, both simultaneously and partially. This is evidenced by the difference in mean values, where the mean values ​​of scientific literacy and student autonomy taught through PjBL were higher. The research findings also indicate that scientific literacy was more significantly influenced compared to student autonomy. Therefore, it can be recommended as an innovative learning approach to enhance both scientific literacy and student autonomy.